2013
DOI: 10.1371/journal.pone.0084967
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy Patterns: Unravelling Systematic Associations between Prescribed Medications

Abstract: ObjectivesThe aim of this study was to demonstrate the existence of systematic associations in drug prescription that lead to the establishment of patterns of polypharmacy, and the clinical interpretation of the associations found in each pattern. MethodsA cross-sectional study was conducted based on information obtained from electronic medical records and the primary care pharmacy database in 2008. An exploratory factor analysis of drug dispensing information regarding 79,089 adult patients was performed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 39 publications
5
57
1
3
Order By: Relevance
“…First, as this study and others have shown, the number of medications increases with number of conditions [20,21]. Second, treatments may interact, leading to side effects [5,7,46] and this has the potential to further increase the volume of work; for example, as new treatments are given to compensate for interactions [47]. Third, multimorbidity is likely to increase healthcare contacts and affect the capacity of the individual to follow therapeutic regimens [48]; for example, those with stroke and comorbid arthritis may find physiotherapy sessions more challenging [49,50].…”
Section: Summary Of Findings and Implicationsmentioning
confidence: 78%
See 1 more Smart Citation
“…First, as this study and others have shown, the number of medications increases with number of conditions [20,21]. Second, treatments may interact, leading to side effects [5,7,46] and this has the potential to further increase the volume of work; for example, as new treatments are given to compensate for interactions [47]. Third, multimorbidity is likely to increase healthcare contacts and affect the capacity of the individual to follow therapeutic regimens [48]; for example, those with stroke and comorbid arthritis may find physiotherapy sessions more challenging [49,50].…”
Section: Summary Of Findings and Implicationsmentioning
confidence: 78%
“…This issue has been gaining prominence [58,59]. Guidelines should be redesigned to take account of comorbidity and treatment burden; for example, by providing guidance on potential interactions from drug combinations commonly prescribed for those with stroke and multimorbidity and how to deal with the possible side effects or interactions that may arise [47]. In the current study, 21.9% of people with stroke had a painful condition, 20.7% had depression and 13.0% had atrial fibrillation, increasing the risk of being prescribed non-steroidal anti-infammatory drugs (NSAIDs), The stroke group comprised 35,690 people, and the stroke-free group comprised 1,388,688 people.…”
Section: Summary Of Findings and Implicationsmentioning
confidence: 99%
“…The existence of patterns of poly-pharmacy showing the non-random associations in drug prescriptions has also been demonstrated. 11 The present work was performed to evaluate whether the DPN is a good approach for studying the complexity of drug prescription in older persons. Specifically, we aimed at generating, analyzing, and comparing a series of DPNs to elucidate the structure of the DPNs and the possible differences due to changes in drug co-prescription across time and space.…”
Section: Introductionmentioning
confidence: 99%
“…New information on transporter mechanisms, which have substrate and end organ specificity, has improved our understanding of inter-organ variability in drug response. Menopause changes cholesterol and bile metabolism and drugs impact key regulators of cholesterol and bile metabolism [13,14]. Bile salts and the gut microbiome provide the steroid substrate precursors essential for steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%